Histone deacetylase 6 plays an important role in TGF-β-induced murine Treg cell differentiation by regulating cell proliferation - Ji Hyeon Lee; Hyeong Su Kim; Sung Woong Jang; Gap Ryol Lee (Scientific Reports, 2022)
Abstract Regulatory T (Treg) cells maintain immune homeostasis by preventing abnormal or excessive immune responses. Histone deacetylase 6 (HDAC6) regulates expression of Foxp3, and thus, Treg cell differentiation; however, its role in Treg cell differentiation is unclear and somewhat controversial. Here, we investigated the role of HDAC6 in TGF-β-induced murine Treg cells. HDAC6 expression was higher in Treg cells than in other T helper cell subsets. Pharmacological inhibitors of HDAC6 selectively inhibited Treg cell differentiation and suppressive function. A specific HDAC6 inhibitor induced changes in global gene expression by Treg cells. Of these changes, genes related to cell division were prominently affected. In summary, HDAC6 plays an important role in TGF-β-induced murine Treg cell differentiation by regulating cell proliferation.